Validation of an extrinsic compression and early ambulation protocol after diagnostic transfemoral cerebral angiography: a 5-year prospective series. (23rd January 2019) - Tonetti, Daniel A; Ferari, Christopher; Perez, Jennifer; Ozpinar, Alp; Jadhav, Ashutosh P; Jovin, Tudor G; Gross, Bradley A; Jankowitz, Brian Thomas
Abstract : Background and purpose: Access-site complications constitute a substantial portion of the morbidity associated with transfemoral cerebral angiography, yet no standardized protocol exists for femoral closure and practice patterns vary widely. The objective of this single-arm prospective cohort study was to validate the efficacy and safety of a standardized femoral closure strategy for all diagnostic angiography, regardless of antiplatelet regimen. Methods: A single-arm, prospective study was designed enrolling consecutive patients undergoing diagnostic transfemoral cerebral angiography by a single neurointerventional surgeon from March 2013 – March 2018. The closure protocol consisted of 20 minutes of manual compression to the site of arterial access and 2 hours of bedrest. The primary outcome was hematoma or oozing after manual compression. Demographic, clinic, and laboratory data were collected and analyzed, and patients were stratified by antiplatelet use. Results: Of 525 angiograms, 263 (50.1%) were on patients taking antiplatelet medication, with 66 (12.6%) on dual antiplatelet regimens. Five patients (0.95% of all patients) met the primary outcome: in all five cases, there was no further oozing or enlarging hematoma after the additional compression period. There were not significant differences in primary outcome in groups stratified by antiplatelet use, and there were no instances of delayed hematoma, pseudoaneurysm, or arteriovenous fistula. Conclusion: In this single-arm cohort study of 525 consecutive transfemoral angiograms with a standardized extrinsic compression protocol, hemostasis was achieved without complication in >99% regardless of antiplatelet strategy. This protocol is effective and safe for diagnostic transfemoral angiography regardless of a patient's antiplatelet use.